Geometric morphometric analysis of projectile points from the Southwest United States - Bischoff, Robert J. (Peer Community Journal, 2023)

(untitled)
Traditional analyses of projectile points often use visual identification, the presence or absence of discrete characteristics, or linear measurements and angles to classify points into distinct types. Geometric morphometrics provides additional tools for analyzing, visualizing, and comparing projectile point morphology utilizing the whole or parts of the form in either two or three dimensions. This study is an analysis of the effectiveness of geometric morphometric methods for identifying technological similarity in 2D projectile point outlines for previously classified late prehistoric projectile points found in the U.S. Southwest and unclassified projectile points from Tonto Basin, Arizona. Various methods from geometric morphometrics were compared to determine which method best reproduced the original classification scheme. Elliptical Fourier analysis was compared with various configurations of semilandmark and landmark analyses using generalized Procrustes analysis. These methods were applied to the complete projectile point form, and the landmark analysis was also applied to half of the lower quadrant of the projectile point—essentially one corner of the projectile point. The landmark analysis applied to the corner of the projectile point provided the best results. This method was then applied to the Tonto Basin points. Hierarchical clustering was used on the Tonto Basin projectile point morphometric data to explore the variation in shapes between sites. To demonstrate that geometric morphometric methods can be used without relying on typologies, a network analysis of the morphometric distances was also conducted. This network graph produced distinct clusters of technological similarity in projectile point outlines, while also showing the continuous variation between points. These results demonstrate the effectiveness of geometric morphometrics for the 2D analysis of late prehistoric arrow points in the U.S. Southwest.